DISPARAGEMENT OF A BUSINESS, ITS PRODUCTS OR ITS SERVICES: FREEDOM OF EXPRESSION OF CONSUMERS AND THE PUBLIC - J Neethling; JM Potgieter (Obiter, 2022)
In two recent cases of the Supreme Court of Appeal which attracted much attention in the media as the so-called “Worst 4 x 4 x Far [Isuzu bakkie]” and “Black Labour [Black Label], White Guilt [Carling Beer]” cases (Delta Motor Corporation (Pty) Ltd v Van der Merwe 2004 6 SA 185 (SCA) and Laugh it Off Promotions CC v South African Breweries International (Finance) BV t/a Sabmark International 2005 2 SA 46 (SCA)), the following question arose: to what extent is the public (consumers and private undertakings) free to disparage the business, products or services (including trade marks) of an entrepreneur? Two forms of delict may be relevant in this regard: first, nondefamatory disparagement which infringes the goodwill of a business, irrespective of whether the disparagement is false (so-called injurious falsehood) or true; and, second, defamation of a business enterprise (including its goods or services). (In passing, it may also be mentioned that in instances of passing off and leaning on as forms of unlawful competition, where an entrepreneur misappropriates a rival’s distinctive or advertising marks, disparagement may (indirectly) even lie in the fact that the perpetrator’s own performance is of a bad quality and that the public, because of their contact with this performance, forms a lower opinion of the rival’s performance as a result of the association between the two performances (see Van Heerden and Neethling Unlawful Competition (1995) 181 fn 184, 195, 203 fn 19 and 283). The aggrieved party may suffer damage as a result of such injury to its business reputation and consequent loss of custom (see eg Brian Boswell Circus (Pty) Ltd v Boswell-Wilkie Circus (Pty) Ltd 1985 4 SA 466 (A) 478; Capital Estate and General Agencies (Pty) Ltd v Holiday Inns Inc 1977 2 SA 916 (A) 931-932; Truck and Car Co Ltd v Kar-N-Truk Auctions 1954 4 SA 552 (A) 559; Volkskas Bpk v Barclays Bank (DC&O) 1952 3 SA 343 (A) 347; and Lorimar Productions Inc v Sterling Clothing Manufacturers (Pty) Ltd, Lorimar Productions Inc v OK Hyperama Ltd, Lorimar Productions Inc v Dallas Restaurant 1981 3 SA 1129 (T) 1138). These forms of disparagement are, however, not relevant to the present discussion.)